Early esophageal cancer in Europe: endoscopic treatment by endoscopic submucosal dissection - Probst, Andreas; Aust, Daniela; Märkl, Bruno; Anthuber, Matthias; Messmann, Helmut (Endoscopy, 2015)
Background and study aims: Endoscopic resection is the standard treatment for superficial esophageal cancer. Data on early adenocarcinoma (EAC) are widely restricted to endoscopic mucosal resection (EMR), whereas large studies have been published on endoscopic submucosal dissection (ESD) for early squamous cell carcinoma (ESCC). ESD has potential advantages regarding en bloc and R0 resection rates, which have been demonstrated for ESCC. However, studies have failed to confirm these advantages in EAC. The aim of this study was to investigate the efficacy of ESD in early esophageal cancer. Patients and methods: A total of 111 early esophageal cancers (87 EACs and 24 ESCCs) were resected by ESD at a German tertiary referral center. A total of 60 EACs were resected within Barrett’s segments ≤ M3. Resection rates, complications, and follow-up data were recorded prospectively. Results: En bloc resection rates were 95.4 % for EAC and 100 % for ESCC (P = 0.575), and R0 resection rates were 83.9 % and 91.7 %, respectively (P = 0.515). The R0 resection rate was higher in Barrett’s ≤ M3 vs. > M3 (90 % vs. 70.4 %; P = 0.029). The curative resection rate was 72.4 % for EAC vs. 45.8 % for ESCC (P = 0.026). Endoluminal recurrence was observed in 2.4 % of EACs (8 % in Barrett’s > M3, 0 % in Barrett’s ≤ M3), and 0 % of ESCCs. Complications included strictures (11.7 %) and bleedings (0.9 %), but no perforation. Disease-specific survival was 97.7 % (EAC) and 95.8 % (ESCC), and overall survival was 96.6 % (EAC) and 66.7 % (ESCC) over a mean follow-up period of 24.3 months and 38.0 months, respectively.Conclusions: ESD was shown to be a safe resection method, achieving high R0 resection rates in both EAC and ESCC. Recurrence rates were low. To improve R0 resection within long Barrett’s segments, diagnosis of the lateral extension of the lesion needs to be improved.